2020
DOI: 10.1016/j.immuni.2020.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Chemosensory Cell-Derived Acetylcholine Drives Tracheal Mucociliary Clearance in Response to Virulence-Associated Formyl Peptides

Abstract: Highlights d Tracheal chemosensory cells recognize virulence-associated formyl peptides d This activates a TRPM5-dependent pathway, triggering acetylcholine release d Acetylcholine released from chemosensory cells activates mucociliary clearance d Mice with genetic impairment of this pathway are more susceptible to infection

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
126
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 77 publications
(130 citation statements)
references
References 93 publications
2
126
1
1
Order By: Relevance
“…intact cholinergic constriction evoked by electrical field stimulation. The effect of a formylated bacterial peptide on stimulating particle transport speed, however, was almost fully lost (Perniss et al 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…intact cholinergic constriction evoked by electrical field stimulation. The effect of a formylated bacterial peptide on stimulating particle transport speed, however, was almost fully lost (Perniss et al 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The evocation of respiratory reflexes reflected on the sharp changes in respiration combined with abrupt decreases in respiratory rate. Apart from the bitter substances, tuft cells are also capable of detecting bacterial products in airway lining fluid and thus conduct mucociliary clearance ( Krasteva et al, 2012a ; Hollenhorst et al, 2020 ; Perniss et al, 2020 ). Using Avil cre :Chat fl/fl mouse model which retained neural cholinergic signaling but conditional loss of ACh synthesis in tuft cells, Perniss et al demonstrated that by detecting formylated bacterial peptides, tuft cells rather than cholinergic nerves released ACh activating mucociliary clearance ( Perniss et al, 2020 ).…”
Section: Pathophysiological Roles Of Ach Produced By Tuft Cellsmentioning
confidence: 99%
“…The administration of high concentration of atropine inhibiting ASM constriction was a non-specific effect and the inhibitory effect of atropine did not indicate that serotonin-induced ASM constriction was in a muscarinic receptor-independent manner. Secondly, another nonnegligible reason is the different situations between trachea and bronchi that cholinergic chemosensory cells exist in the tracheal rather than bronchial mucosa ( Krasteva et al, 2012a ; Perniss et al, 2020 ). Epithelial cell has been identified a source of ACh in the airways, we should not exclude the possibility that epithelial cells-derived ACh participated in ASM constriction.…”
Section: Pathophysiological Roles Of Ach Produced By Tuft Cellsmentioning
confidence: 99%
See 2 more Smart Citations